PENGEMBANGAN MEDIA GAME ULAR TANGGA BERBASIS FLASH PADA MATERI TEORI ATOM KELAS X SMA NEGERI 2 PONTIANAK - Surati Surati; Dini Hadiarti; Tuti Kurniati (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTThis study was initiated by the ineffectiveness and inefficiency of the media used by the teacher in Atomic Theory class. As a result, proper media such as flash media-based snakes and ladders game is urgently needed. Thus, this study aimed at developing a practical, valid, effective, and applicable flash media -based snakes and ladders game on Atomic Theory for grade X students of SMA Negeri 2 Pontianak. A 3D (Define, Design, and Develop) development model suggested by Thiagarajan was carried out in this study. The data collection technique used were indirect communication, and measurement. While the instruments used were pre-test and post test questions, and the test sheets of learning outcomes. The study revealed that flash media-based snakes and ladders game was considered valid (3,52) and attracted positive response from both students and teachers with the practicality score of 85,78 % and 75 %. This media has fulfilled the effectiveness aspect, as well, as there were significant difference of before and after the media used (<0,05). Based on the results of data analysis, flash media-based snakes and ladders game is applicable to be used as the teaching materials in learning process.Keywords: flash media-based game, atomic theory, snakes and ladders